AKTA PENGIKATAN JUAL BELI SEBAGAI DASAR PENGALIHAN KEPEMILIKAN RUMAH (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 396 PK/PDT/2014 - MAHYARUDDIN BATUBARA (PREMISE LAW JURNAL, 2016)
Sales contract on land and building in cash signed by a Notary usually causes dispute because after the contract has been made the seller does not do physicall delivery on the object since he feels that the contract has not yet been made before the real offcial empowered to drow it up. In consequence, the buyer files a complaint ti the court. The problems of the reseach were as follows: how about the legal consequence of making a sales contract on certified land and building, how about the consequence of not continuing to follow up sales contract, and how about judge’s legal consideration in the supreme court’s ruling No.396 PK/Pdt/2014. Keywords : certificate, sales contract, transfer of tittle